Entrepreneurial Competence and MSME Performance: Islamic Business Ethics as Intervening Variable - Septy Holisa Umamy; Muhammad Rizqi Ramadhani; Renata Eka Pratiwi; Kristina Dwi Putri; Melisa Auril Putri Hasania (IECON: International Economics and Business Conference, 2025)
This study aims to examine the influence of entrepreneurial competence on the performance of MSME actors, and to analyze the role of Islamic business ethics as an intervening variable in the relationship. The focus of this study is directed at MSME actors in Jember Regency, considering the high number of micro-enterprises that are the mainstay of the regional economy. This study uses a quantitative approach with a multivariate analysis method based on Partial Least Square Structural Equation Modeling (PLS-SEM), with the help of SmartPLS software version 3.0. The sample used was 100 MSME actors, selected using purposive sampling techniques based on certain criteria. The results of the analysis show that entrepreneurial competence has a significant direct influence on the performance of MSME actors. In addition, entrepreneurial competence has also been proven to directly influence the application of Islamic business ethics in business activities. Other findings show that Islamic business ethics directly influence the performance of MSME actors in Jember Regency. Furthermore, Islamic business ethics also acts as a significant intervening variable, which strengthens the relationship between entrepreneurial competence and MSME performance. This means that the higher the entrepreneurial competence possessed by business actors, if accompanied by the implementation of good Islamic business ethics, it will have a more optimal impact on improving business performance. This study provides theoretical contributions to the development of an entrepreneurial model based on Islamic ethical values, and offers practical implications for MSME actors and policy makers in designing business capacity development programs that not only emphasize technical competence aspects, but also moral and spiritual integrity.